ECONOMIC ANALYSIS OF LAND SPECULATION AND ITS IMPACT ON LAND VALUE INFLATION: THE ROLE OF ILLEGAL ACTORS IN LAND RIGHTS TRANSFER MANIPULATION - Sendi Sanjaya; Gunawan Widjaja (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Land speculation is one of the economic activities that has the potential to cause significant land value inflation. This activity not only disrupts the balance of the land market but also has negative socio-economic impacts on society and development. In this context, the role of illegal actors becomes crucial as they often manipulate the land rights transfer process through illegal means, such as document forgery and illicit transactions, which contribute to artificial increases in land prices. This study employs a literature review. The analysis results indicate that land rights manipulation by illegal actors exacerbates inequality in land ownership and increases price instability in the land market. Therefore, strict policy interventions and effective oversight are necessary to prevent harmful speculative activities and protect the rights of communities to land.